MANAJEMEN KELAS YANG EFEKTIF - ASTUTI Astuti (Adaara: Jurnal Manajemen Pendidikan Islam, 2019)
Abstrak. Class management is any effort directed at creating an atmosphere of learning that is effective and enjoyable and can motivate students. Class management generally aims to increase effectiveness and efficiency in achieving learning objectives. In addition, classroom management also aims to create a comfortable classroom atmosphere where teaching and learning take place. Therefore, in an effort to realize effective classroom management, it must pay attention to the principles of effective classroom management, class management approaches and implement the planning, implementation, and assessment of class management programs.